The Combination Vaccine Adjuvant System Alum/c-di-AMP Results in Quantitative and Qualitative Enhanced Immune Responses Post Immunization - Ebensen, Thomas; Delandre, Simon; Prochnow, Blair; Guzmán, Carlos A.; Schulze, Kai (Frontiers in Cellular and Infection Microbiology, 2019)
The development of new effective vaccines strongly depends on adjuvants and formulations able to stimulate not only strong humoral responses against a certain pathogen but also effector as well as memory CD4+ and CD8+ T cells (Dubensky et al., 2013). However, the majority of vaccines licensed for human use or currently under clinical investigation fail to stimulate efficient cellular responses. For example, vaccines against hepatitis B virus (HBV), human papillomavirus (HPV), diphtheria, tetanus and influenza are usually administered by intramuscular (i.m.) injection and contain aluminum salts (alum) as adjuvant. Alum has been shown to stimulate Th2 immune cells resulting in increased production of antigen-specific antibodies but to be incapable of stimulating robust Th1 or cytotoxic responses. To overcome such limitations recent research has focused on the development of adjuvant combinations (e.g., MF59, AS03 or AS04) to not only further strengthen antigen-specific immune responses but to also allow their modulation. We have shown previously that bis-(3′,5′)-cyclic dimeric adenosine monophosphate (c-di-AMP) constitutes a promising adjuvant candidate stimulating both effective Th1/Th2 and cytotoxic immune responses when included in mucosal or parenteral vaccine formulations. In the present work we demonstrate that c-di-AMP can be also combined with other adjuvants like alum resulting in increases in not only humoral responses but more striking also in cellular immune responses. This leads to improved vaccine efficacy against intracellular pathogens.